New insights into the role of the aryl hydrocarbon receptor in the function of CD11c+ cells during respiratory viral infection. Issue 6 (19th March 2014) - Jin, Guang‐Bi; Winans, Bethany; Martin, Kyle C.; Lawrence, B. Paige
<x xml:space="preserve">Abstract</x> The aryl hydrocarbon receptor (AHR) has garnered considerable attention as a modulator of CD4+ cell lineage development and function. It also regulates antiviral CD8+ T‐cell responses, but via indirect mechanisms that have yet to be determined. Here, we show that during acute influenza virus infection, AHR activation skews dendritic‐cell (DC) subsets in the lung‐draining lymph nodes, such that there are fewer conventional CD103+ DCs and CD11b+ DCs. Sorting DC subsets reveals AHR activation reduces immunostimulatory function of CD103+ DCs in the mediastinal lymph nodes, and decreases their frequency in the lung. DNA‐binding domain Ahr mutants demonstrate that alterations in DC subsets require the ligand‐activated AHR to contain its inherent DNA‐binding domain. To evaluate the intrinsic role of AHR in DCs, conditional knockouts were created using Cre‐LoxP technology, which revealed that AHR in CD11c+ cells plays a key role in controlling the acquisition of effector CD8+ T cells in the infected lung. However, AHR within other leukocyte lineages contributes to diminished naïve CD8+ T‐cell activation in the draining lymphoid nodes. These findings indicate DCs are among the direct targets of AHR ligands in vivo, and AHR signaling modifies host responses to a common respiratory pathogen by affecting the complex interplay of multiple cell types.